Etnobotani Upacara Adat di Kecamatan Paron, Kabupaten Ngawi dan Pemanfaatannya sebagai E-Booklet - May Dinda Riski Ardita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Indonesia possesses extensive cultural diversity encompasssing ethnic group, customs, traditions, languages, belief systems, and ritual practices. Tradititonal ceremonies represent an important form of intangible cultural heritage that contributes to social cohesion within communities. However, these practices fase increasing challenges due to modernization, digital transformation, and urbanization, which have led to declining youth participation. This study aims to explore traditional ceremonies that remain actively practiced in Paron District, Ngawi Regency, East Java, identify plant species used in these rituals, analyze the utilized plant parts and their sources, examine the associated philosophical meanings, and develop a validated ethnobotanical e-booklet as an educational medium. This research amployed a descriptive exploratory design intergrating qualitative and quantitative approaches. Data were collected through semi structured interviews, participant observation, and documentation. Informants were selected using key informant determination, purposive sampling, and snowball sampling techniques. A total of 24 informants from six villages participated in the study. The results revealed that 13 types of traditional ceremonies related to agriculture, birth, marriage, communal rituals, and death are still practiced. All ceremonies involved plants as essential components of ritual equipment and offerings. A total of 85 plant species from 37 families were documented, with Fabaceace being the most dominant family. Herbs were the most common growth form, a fruits and leaves were the most frequently used plant parts, indicating sustainable utilization practices. Use value analysis identified 21 plant species with high cultural importance. Overall, tradtional ceremonies in Paron District reflect values of gratitude, harmony enviromental conservation, and relationship between humans, nature, and God. The ethnobotanical findings were compiled into an e-booklet focusing on birt-related ceremonies, which was assessed as highly feasible with minor revisions. This study contributes to the preservation of local wisdom and provides accessible educational resources for the broader community.
:: Finalisasi Repositori File 6 Juni 2026_Kurnadi
Keywords: Etnobotani; upacara adat; Tumbuhan; Ngawi